Development of a centralized shariah governance framework for islamic banks in Bangladesh - Alam, Md Kausar (2019)
Shariah Governance is defined as a set of institutional arrangements through which Islamic Financial Institutions ensure that there is an effective independent oversight of Shariah compliance over its products, instruments, operations, practices, management, etc. Apart from that, the purpose of the Shariah governance framework is to ensure the smooth functioning of Islamic Financial Institutions. At the moment, Bangladesh has no comprehensive Shariah governance structure including the Shariah governance framework and full-fledged legal framework that govern the operation of Islamic banking activities, hence hinder the growth of this industry in the country. This lack of a mechanism that governs Islamic banking activities creates regulatory gaps and confusions among its stakeholders especially with regards to Shariah compliance. The main objective of this study is to investigate and evaluate the current Shariah governance framework practices in Bangladesh and further to develop a centralized Shariah governance framework for Islamic banks. To achieve this objective, the study implements a case study and uses of semi-structured personal interviews with 17 respondents who have relevant backgrounds on Shariah governance of Islamic banks in Bangladesh. Furthermore, the study uses agency theory, stewardship theory, stakeholder theory, and new institutional theory as the basis for the study. This study finds that in the current practices, every Islamic bank has its Shariah governance guidelines but in the real sense, they are not adequately and effectively practicing the principles of Shariah due to high-profit intention, board of directors’ influence, and lack of accountability. Furthermore, the Shariah supervisory board and the Shariah executives are not independent in performing their functions. The board of directors and management also use themselves as a showcase to accomplish their goals and to maximize profit in the name of Islam. In addition, this study also finds that Islamic banks are also facing pressures from the society, culture, government administrations, politics, existing banking industry, conventional banks, bankers, and secular people in their policymaking and operational activities. Besides, Islamic banks develop an additional image in the overall banking sector of Bangladesh through their corporate social responsibility. Hence, to ensure the smooth functioning of Islamic banks in Bangladesh, this study proposes a centralized Shariah governance framework which comprises of two-tier Shariah supervisory boards i.e., institutional Shariah supervisory boards and Centralized Shariah supervisory board to monitor the functions of Islamic banks. The study also recommends to set up four departments such as Shariah department, Islamic banking regulation and policy department, Shariah supervision department, and Shariah inspection department under the central bank to enhance the functions of centralized Shariah governance framework. Finally, the central bank can introduce Shariah rating and external Shariah audit through Islamic rating agencies and Islamic chartered accountant firms for transparency and quality compliance, desired by the public and other stakeholders. Centralized Shariah supervisory board will be responsible for the overall Shariah issues of the Islamic banks, and the central bank will implement the suggestions of the Centralized Shariah supervisory board in any Shariah related matters, regulations, and guidelines. The research demonstrates the reasons behind the differences in the mechanisms of Shariah governance practices in the context of Bangladesh which will be beneficial for the central bank and Islamic banks. This proposed centralized Shariah governance framework will be beneficial for the central bank and Islamic banks to explore the Islamic banking industry, its functions, Shariah governance practices, and Shariah compliance quality in Bangladesh. The findings will help them to minimize the misconception, improve Shariah governance practices, and enhance the quality of Shariah compliance and the image of Islamic banks. The government or the central bank can implement this framework or modify this framework for best fitted, to enhance the Shariah governance structure and fulfill the expectations of all concerned stakeholders related to the Islamic banks in Bangladesh. This framework will help the other nations to develop the two-tier Shariah governance framework in centralized Shariah governance framework practicing countries and other Islamic banking practices nations.